Gestión financiera del sector de alimentos y bebidas del Ecuador: Un estudio de los determinantes de rentabilidad - iménez Fárez, Joseph Jasmany (2024)
The food and beverage sector plays a fundamental role in Ecuador’s economy. This sector constitutes an industry responsible for processes related to the food chain, encompassing the production, processing, distribution, and marketing of food products. In this context, the purpose of the research is to identify the factors that effect financial management in the food and beverage sector in Ecuador. For this, a mixed approach with a cross-sectional design was used. First, a characterization of the sector was conduced with a descriptive scope. Subsequently, through a correlational analysis, the direction and strength of the variables affecting financial management indicators were determined. Similarly, a multiple regression model was used to identify the variables that influence the profitability of companies operating in the food and beverage sector. The results indicate that companies with greater equity and assets achieve higher profitability and financial stability. Conversely, micro-enterprises and small businesses face greater financial challenges due to their limitations in assets and resources. Additionally, a significant positive relationship was found between net profit and variables such as the number of employees, assets, and sales revenue, indicating that higher productivity and financial capacity lead to better economic outcomes. Finally, it was concluded that asset debt negatively impacts ROA, whereas efficient asset utilization, increased sales, and maintaining an appropriate capital structure improve ROE. The findings reveal that, in the food and beverage sector, larger companies demonstrate higher profitability and financial stability, while micro and small enterprises encounter greater difficulties in self-financing, as they often rely heavily on external funding. Consequently, they incur significant financial liabilities with banking institutions, reflecting higher operational cost and generate economic challenges and impact their profitability.